A Comparison of Web-Based with Traditional Classroom-Based Training of Lung Ultrasound for the Exclusion of Pneumothorax. (July 2016) - Edrich, Thomas; Stopfkuchen-Evans, Matthias; Scheiermann, Patrick; Heim, Markus; Chan, Wilma; Stone, Michael B.; Dankl, Daniel; Aichner, Jonathan; Hinzmann, Dominik; Song, Pingping; Szabo, Ashley L.; Frendl, Gyorgy; et al.
Abstract : BACKGROUND: Lung ultrasound (LUS) is a well-established method that can exclude pneumothorax by demonstration of pleural sliding and the associated ultrasound artifacts. The positive diagnosis of pneumothorax is more difficult to obtain and relies on detection of the edge of a pneumothorax, called the "lung point." Yet, anesthesiologists are not widely taught these techniques, even though their patients are susceptible to pneumothorax either through trauma or as a result of central line placement or regional anesthesia techniques performed near the thorax. In anticipation of an increased training demand for LUS, efficient and scalable teaching methods should be developed. In this study, we compared the improvement in LUS skills after either Web-based or classroom-based training. We hypothesized that Web-based training would not be inferior to "traditional" classroom-based training beyond a noninferiority limit of 10% and that both would be superior to no training. Furthermore, we hypothesized that this short training session would lead to LUS skills that are similar to those of ultrasound-trained emergency medicine (EM) physicians. METHODS: After a pretest, anesthesiologists from 4 academic teaching hospitals were randomized to Web-based (group Web), classroom-based (group class), or no training (group control) and then completed a posttest. Groups Web and class returned for a retention test 4 weeks later. All 3 tests were similar, testing both practical and theoretical knowledge. EM physicians (group EM) performed the pretest only. Teaching for group class consisted of a standardized PowerPoint lecture conforming to the Consensus Conference on LUS followed by hands-on training. Group Web received a narrated video of the same PowerPoint presentation, followed by an online demonstration of LUS that also instructs the viewer to perform an LUS on himself using a clinically available ultrasound machine and submit smartphone snapshots of the resulting images as part of a portfolio system. Group Web received no other hands-on training. RESULTS: Groups Web, class, control, and EM contained 59, 59, 20, and 42 subjects. After training, overall test results of groups Web and class improved by a mean of 42.9% (±18.1% SD) and 39.2% (±19.2% SD), whereas the score of group control did not improve significantly. The test improvement of group Web was not inferior to group class. The posttest scores of groups Web and class were not significantly different from group EM. In comparison with the posttests, the retention test scores did not change significantly in either group. CONCLUSIONS: When training anesthesiologists to perform LUS for the exclusion of pneumothorax, we found that Web-based training was not inferior to traditional classroom-based training and was effective, leading to test scores that were similar to a group of clinicians experienced in LUS. Abstract : Supplemental Digital Content is available in the text.Published ahead of print May 6, 2016